An analysis of the airport experience from an air traveler perspective. (September 2017) - Wattanacharoensil, Walanchalee; Schuckert, Markus; Graham, Anne; Dean, Alison
Abstract: This study investigates the nature of airport experience (AE) from the perspective of air travelers. This study elaborates experiential components within the airport context and highlights the associations among the components of this experience through text analysis. This study also aims to clarify how air travelers perceive airports in relation to destinations. The analysis of passenger reviews on Skytrax indicates that AE differs from the concepts of customer and tourist experiences, because hedonic and aesthetic consumptions are not primarily associated with the memorable feelings of consumers and tourists, but with aspects of functional experience and service personnel. This study reviews three aspects that air travelers associate airports with a destination. First, an airport is a representative of a destination. Second, an airport exhibits the positive characteristics of a destination. Finally, an airport is perceived as an internal component of tourism experience. This study provides theoretical and managerial implications for airport and tourism industries.